1962
DOI: 10.1152/ajplegacy.1962.203.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin and cardiovascular system: estimation of half-life

Abstract: Synthetic bradykinin in postpartal women produced a decrease in systolic and diastolic blood pressure, reduction of pulse pressure, and increased heart rate and respiration. The threshold dose for single intravenous injections was approximately 0.1 µg/kg, and that for intravenous infusions approximately 0.125 µg/kg/min. For the change in diastolic blood pressure, a linear dose-response curve was found in the semilogarithmic system in the range of 0.125– 1.25 µg/kg/min. In intravenous infusions, the maximal eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1965
1965
1989
1989

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…It was possible to apply bradykinin repeatedly at a dose of 100 pmol in intervals of 10 min showing that there is no development of tolerance to this dose. The effect only lasted for approximately 1 min, confirming the short halflife of bradykinin in blood, calculated to be less than 30s in man (Saameli & Eskes, 1962), in the dog (McCarthy et al, 1965) and in the cat (Ferreira & Vane, 1967b). An i.a.…”
Section: Agonistic and Antagonistic Propertiessupporting
confidence: 57%
“…It was possible to apply bradykinin repeatedly at a dose of 100 pmol in intervals of 10 min showing that there is no development of tolerance to this dose. The effect only lasted for approximately 1 min, confirming the short halflife of bradykinin in blood, calculated to be less than 30s in man (Saameli & Eskes, 1962), in the dog (McCarthy et al, 1965) and in the cat (Ferreira & Vane, 1967b). An i.a.…”
Section: Agonistic and Antagonistic Propertiessupporting
confidence: 57%
“…The rise in kininogen levels during pregnancy reported by Periti & Gasparri (1966) (Saameli & Eskes, 1962).…”
Section: Discussionmentioning
confidence: 90%
“…It now seems likely that the activity is due, at least in part, to the prostaglandins (Karim, 1969), but the belief that polypeptides may contribute to it has led several workers to study the precursors of the plasma kinins (kininogens) in the blood in order to determine the extent to which they are mobilized in pregnancy and labour. Kininogen rather than kinin levels have been estimated because, until recently, it has not been possible to determine the free kinin levels in plasma with any degree of accuracy, since rapid enzyme action gives an extremely short half-life to the kinins, both in vivo and in vitro (Saameli & Eskes, 1962). Martinez, Carvalho & Diniz (1962) found that the kininogen content of plasma fell during labour but returned to prepartum values in the puerperium.…”
Section: Introductionmentioning
confidence: 99%
“…The half-life of synthetic bradykinin in the body is less than 05 min (Saameli & Eskes, 1962;McCarthy, Potter & Nicolaides, 1965), and kinin activity is easily lost during purification. The inadvertent production of kinins during sampling and the separation of plasma is an even greater hazard.…”
Section: Estimation Of Kinins In Man Discussionmentioning
confidence: 99%